Transmission patterns of eukaryotic transposable elements - arguments for and against horizontal transfer - Michael P. Cummings (Trends Ecol EvolTrends Ecol Evol, 1994)
Recent studies have demonstrated that several classes of transposable elements are widely distributed within eukaryotes. Horizontal transmission of these transposable elements has often been invoked in order to explain the observed variation and relationships within and between species. These same patterns of variation and relationships, however, may originate from processes that do not involve the lateral transfer of genetic material across species.